2013
DOI: 10.1155/2013/715618
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Parenting Factors with Adolescent Body Mass Index in an Underserved Population

Abstract: Background. The current study examined parental factors related to risk of adolescent obesity within the context of a family systems framework. Methods. Seventy predominantly African American, low-income caregiver-adolescent dyads participated in the study. Validated measures of parental perceived child risk for development of type 2 diabetes mellitus, parental limit setting for sedentary behavior, and parental nurturance were evaluated as predictors of adolescent body mass index. Results. In this cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
(40 reference statements)
0
6
0
2
Order By: Relevance
“…Parent age, gender, education, employment, country of birth, and years living in the United States, child age, and child gender accounted for significant differences across multiple parenting practices, which is consistent with previous observations that parenting practices differ by sociodemographic characteristics. 27,29,[40][41][42] Deepening our understanding of these sociodemographic disparities will improve our abilities to develop culturally appropriate interventions. In this sample of overweight and obese children enrolled in a familyfocused weight management program with their parent/ caregiver at baseline, parents/caregivers reported moderate-high levels of monitoring, limit setting SS, limit setting SM, and reinforcement as well as moderate-to-low levels of pressure to eat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parent age, gender, education, employment, country of birth, and years living in the United States, child age, and child gender accounted for significant differences across multiple parenting practices, which is consistent with previous observations that parenting practices differ by sociodemographic characteristics. 27,29,[40][41][42] Deepening our understanding of these sociodemographic disparities will improve our abilities to develop culturally appropriate interventions. In this sample of overweight and obese children enrolled in a familyfocused weight management program with their parent/ caregiver at baseline, parents/caregivers reported moderate-high levels of monitoring, limit setting SS, limit setting SM, and reinforcement as well as moderate-to-low levels of pressure to eat.…”
Section: Discussionmentioning
confidence: 99%
“…Based on results of the Aventuras para Niños study, 22,[26][27][28][29] we hypothesized that the parenting practices monitoring, discipline, limit setting SS, and limit setting SM would be associated with healthier reports of the home environment, whereas pressure to eat would be associated with less-healthful reports of the home environment.…”
mentioning
confidence: 99%
“…Two strategies that were also associated with the children's nutritional status were limits and discipline. In this respect, the evidence indicates that demanding parents' imposition of rules can provoke sedentary conducts in the children ( 17 ) and also alter their internal hunger and satiety mechanisms ( 18 ) , all the more when considering that these strategies distinguish the authoritarian parental style, which is predominant in Mexican parents, characterizing by the exercise of control as manipulation of the child's feelings and bonding, without limits and strict rules, which could increase the calorie and fat intake ( 19 ) and, therefore, the BMI levels.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has long been a major health concern among adults, but its increasing prevalence rates and associated health risks in children and adolescents over the last three decades have made it a public health priority. 1 Childhood obesity has reached epidemic proportions worldwide despite major efforts to promote weight reduction, with more than 75% of overweight and obese children living in low and middle income countries, particularly in urban settings. 2…”
Section: Introductionmentioning
confidence: 99%
“… 13 Recent reviews have indicated the importance of parental involvement and parental monitoring of child health behaviours in preventing and treating childhood obesity. 1 Family meal setting has the potential to positively impact the dietary intake of children. Research has also indicated a positive association between family meal frequency and improved dietary quality among children and adolescents.…”
Section: Introductionmentioning
confidence: 99%